2011
DOI: 10.1152/ajpregu.00211.2011
|View full text |Cite
|
Sign up to set email alerts
|

Muscle protein metabolism responds similarly to exogenous amino acids in healthy younger and older adults during NO-induced hyperemia

Abstract: The combination of increasing blood flow and amino acid (AA) availability provides an anabolic stimulus to the skeletal muscle of healthy young adults by optimizing both AA delivery and utilization. However, aging is associated with a blunted response to anabolic stimuli and may involve impairments in endothelial function. We investigated whether age-related differences exist in the muscle protein anabolic response to AAs between younger (30 ± 2 yr) and older (67 ± 2 yr) adults when macrovascular and microvasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…The increase in peak intensity and AUC concomitant with a greater increase in the perfusion index (the quotient of AUC and time for FWHM) is consistent with work demonstrating changes in microvascular perfusion and volume but not microvascular blood flow after exercise (20) and with sodium nitroprusside (18). Insulin is well recognized for its capacity to stimulate blood flow and recruitment of the microvasculature (for review, see Ref.…”
supporting
confidence: 81%
“…The increase in peak intensity and AUC concomitant with a greater increase in the perfusion index (the quotient of AUC and time for FWHM) is consistent with work demonstrating changes in microvascular perfusion and volume but not microvascular blood flow after exercise (20) and with sodium nitroprusside (18). Insulin is well recognized for its capacity to stimulate blood flow and recruitment of the microvasculature (for review, see Ref.…”
supporting
confidence: 81%
“…2E), and despite the WP maintaining significantly raised LEU concentrations for longer than the LEAA, there was no additional stimulation of MPS with WP. On this basis, research is needed to define the effects of LEU in the context of AA requirements for muscle health in old age (7,8,15,19,46,55,58).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that attenuation of insulin-induced vasodilation in elderly people may be involved in anabolic resistance. Indeed, sodium nitroprusside, a vasodilatory NO donor, ameliorates the muscle protein anabolic effect and net balance induced by insulin or amino acids in older adults 70,71) . Also, a previous study showed that the amino acid concentration in plasma is more important for mediating protein synthesis than the intramuscular concentration 72) .…”
Section: Effect Of Blood Flow Volume On Skeletal Muscle Protein Metabmentioning
confidence: 99%